Impact Evaluation of the Land Record Management Information System in the Punjab Province, Pakistan - Ullah, Inayat; Hussain, Saqib; Akhoubzi, Wafa; Hussain, Saddam; Riaz Khan, Muhammad; Jamil, Sana; Parveen, Aqsa (KDI School of Public Policy and Management, 2021)
The authors gratefully acknowledge financial support from the KDI School of Public Policy and Management throughout this research. The authors are also grateful to KDIS Prof.Jungho Kim and other anonymous reviewers for constructive feedback during the seminar presentation and peer review process. The KDIS alumnus and World Bank professional Mr.Rony Rodrigo Maximiliano Rodríguez-Ramírez has extended a huge support during the analysis of this work and our team is extremely grateful for his contributions.